THE ANALYSIS OF CIRCUMSTANCES MITIGATING PUNISHMENT NOT REGULATED BY THE CRIMINAL CODE - Komron Tursunmurodov (Scholar Express Journals, 2024)
This article discusses circumstances that are recognized by courts as mitigating punishment in Uzbekistan for committing theft. The article uses around 50 judicial rulings to identify most common circumstances mitigating punishment not explicitly outlined in the Criminal Code of Uzbekistan, rather formed by courts. The article also sheds light on the essence of these circumstances, provides feasible suggestions and urges courts to thoughtfully recognize and justify them in their rulings
Keywords: Mitigating circumstances; Mitigating circumstancesjudgment